Assessing the supply and demand linkage of cultural ecosystem services in a typical county-level city with protected areas in China - Yuqing Zhao; Weibin You; Xueer Lin; Dongjin He (Ecological Indicators, 2023)
The construction of protected areas (PAs) is not only the most effective way to preserve biodiversity resources and the natural heritage, but also provides important cultural ecosystem services (CESs) for satisfying human psychological and spiritual needs and improving human well-being. Knowledge of CESs at the county level is vital for the bottom-up promotion of the overall work of China’s PAs. The assessment and mapping of the spatial pattern of CESs, and their supply and demand relationship in PAs and their surrounding areas, are of great significance for high-quality development planning at the county scale. In our study, we developed an integrated approach to mapping the supply and demand of CESs, and then integrated the SolVES model with social media comments to explore the matching relationship between CESs’ (aesthetic inspiration, education humanities, and recreation and ecotourism) supply and demand using Wuyishan City, China, with its abundant PAs, as a case study. The results showed that the supply of three types of CESs accounting for approximately 70% of the study area was greater than the demand, and thus these CESs have significant future development prospects. The distribution of the three high-supply CESs and tourist destinations showed roughly the same spatial patterns, in which the high-demand hot spots were identified in the south of Wuyishan City. And the total supply and demand levels inside the PAs were much greater than those outside. Therefore, clarifying the matching relationship between supply and demand of CESs at the county level is not only conducive to promoting the sustainable development of natural resources, but also provides a reference for the planning of county-level protection of PAs under each county’s jurisdiction.